THE EFFECTIVENESS OF ABDOMINAL STRETCHING EXERCISE ON THE DEGREE OF PRIMARY DYSMENORRHEA IN STUDENTS OF THE PHYSIOTHERAPY STUDY PROGRAM AT BALI INTERNATIONAL UNIVERSITY - Putu Ayu Purnamasari (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2025)
Primary dysmenorrhea is a common condition experienced by female students of reproductive age and can interfere with quality of life and academic activities. Abdominal stretching exercise (ASE) is a non-pharmacological intervention considered safe and effective for reducing menstrual pain without side effects. This study aimed to determine the effectiveness of ASE in reducing the degree of primary dysmenorrhea among students of the Physiotherapy Study Program at Bali International University. This research employed a pre-experimental design using a one-group pre-test and post-test method involving 19 participants selected through purposive sampling. ASE was conducted twice a week for four weeks. The degree of dysmenorrhea was measured using the WaLIDD questionnaire before and after the intervention. Data analysis was performed using the Wilcoxon Signed Rank Test. The results show a significant reduction in dysmenorrhea levels after the ASE intervention (p < 0.05), with an average decrease of 28.56% in WaLIDD scores. These findings indicate that ASE contributes to abdominal muscle relaxation, improved blood circulation, and stimulation of endorphin release, all of which help reduce menstrual pain. This supports the gate control theory and the role of prostaglandins in menstrual pain mechanisms. In conclusion, abdominal stretching exercise is effective in reducing the severity of primary dysmenorrhea.